Una aproximación a la música andina: el huaino, el harawi y el yaraví - Alcántara Silva, Ynés Victoria (2019)
This work is an approach to the Andean music and it studies the special significance that music has for the people of the Peruvian Andes. The article analyzes the origin and evolution of music genres in the Andean world, whose background belongs to the pre-Hispanic music. Likewise, the work studies the emergence, development and themes of the three known genres of Andean music: huaino, harawi and yaravi. Of these three musical genres, the huaino is the most popular genre of the Andean music; it has varied forms and it iscultivated in all regions of Peru. The harawi is a genre of the prehispanic music that has been preserved with certain characteristics in the people of the countryside. The yaravi is a mestizo music genre that emerges from the evolution of the harawi during the Republican era and it is characterized by expressing the sadness of the human soul.